Effect of TIBW anti-wear coating on cutting tools for milling of nickel alloys on tool wear and integrity of state of the technological surface layer - Habrat, Witold; Tymczyszyn, Jarosław; Skroban, Anna; Karkalos, Nikolaos (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2024)
In the article, research was carried out to determine the impact of the TiBW anti-wear coating on the operational properties of cutting tools for machining nickel alloys. The dynamics of tool wear were determined based on changes in the components of the total cutting force, microscopic observation of wear on the flank surface, and observation of wear based on SEM images. The condition of the technological surface layer was also determined in the form of changes in the microstructure morphology and hardening of the surface layer. The research was compared to a reference tool with the same geometry with an AlTiN coating. It was shown, among other things, that TiBW coatings can be used successfully for cutting tools for machining nickel alloys, and that the wear dynamic is similar to those of tools with the AlTiN coating. The analyses confirmed the significant thermomechanical impact of the cutter during machining, manifested by chipping and a tendency to strengthen the processed material. Based on observations of the microstructure of the surface layer after processing, it was shown that the thermal conductivity of the TiBW coating may be lower than that of the AlTiN coating, which is reflected in the different depths of the thermomechanical interaction zones.